2016
DOI: 10.1371/journal.pone.0158356
|View full text |Cite
|
Sign up to set email alerts
|

Binary Toxin Subunits of Lysinibacillus sphaericus Are Monomeric and Form Heterodimers after In Vitro Activation

Abstract: The binary toxin from Lysinibacillus sphaericus has been successfully used for controlling mosquito-transmitted diseases. An activation step shortens both subunits BinA and BinB before their interaction with membranes and internalization in midgut cells, but the precise role of this activation step is unknown. Herein, we show conclusively using three orthogonal biophysical techniques that protoxin subunits form only monomers in aqueous solution. However, in vitro activated toxins readily form heterodimers. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
(53 reference statements)
2
10
0
Order By: Relevance
“…Another problem with a report that BinA and BinB prepared separately and then mixed together formed a tetramer 28 is that in a subsequent study it was shown the Ls protein complex studied 29 by the former group was a spore coat protein complex, not the Bin toxin. In other studies it has been suggested reassociation of BinA and BinB may be required for important conformational changes essential to both molecules so that activated Bin can bind receptors, interact with membrane lipids for additional structural alterations, and induce its internalization 18 , 20 , 27 . We do not question these results under the conditions tested, but our in vivo results reported here provide strong evidence that BinA once activated is highly toxic without requiring BinB for conformational changes, nor does it appear to require interactions with microvillar membrane lipids for toxicity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another problem with a report that BinA and BinB prepared separately and then mixed together formed a tetramer 28 is that in a subsequent study it was shown the Ls protein complex studied 29 by the former group was a spore coat protein complex, not the Bin toxin. In other studies it has been suggested reassociation of BinA and BinB may be required for important conformational changes essential to both molecules so that activated Bin can bind receptors, interact with membrane lipids for additional structural alterations, and induce its internalization 18 , 20 , 27 . We do not question these results under the conditions tested, but our in vivo results reported here provide strong evidence that BinA once activated is highly toxic without requiring BinB for conformational changes, nor does it appear to require interactions with microvillar membrane lipids for toxicity.…”
Section: Discussionmentioning
confidence: 95%
“…Whereas Bin’s intoxication has been well described cytologically 5 , 16 18 , its mode of action at the molecular level remains unknown. In many studies over the past decade it appears to be assumed that BinA and BinB cystallize separately in Ls, dissolve after ingestion in the midgut, are activated, and then associate to form an activated dimer or tetramer 20 22 , 27 (2BinA + 2BinB; see Fig. 6) 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the cytotoxic effect on HepG2 cells caused by the combination of Bin subunits in comparison to individual Bin toxin subunits observed in the present study was in concordance with a previous report by Chankamngoen et al [ 11 ]. In fact, Surya et al [ 16 ] indicated that change in conformational state of Bin toxin monomeric subunits to heterodimeric form occurs when present together in an equimolar ratio in an aqueous solution. The formation of heterodimers in BinA + BinB might affect the interaction of Bin toxin with membrane or with the targeted receptor in susceptible cancer cell lines, resulting in the difference in cytotoxic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the transmembrane helices of XaxA that fortify the inner ring of helices of XaxB, do not completely span the membrane ( Figure S10). The arrangement of the components clearly shows that XaxAB is not a binary toxin as suggested [14,15], but rather a bi-component toxin, such as BinAB from Lysinibacillus sphaericus [26,27] and leukocidin A & B (LukGH and SF) from Staphylococcus aureus [28,29] where both proteins contribute to building the pore.…”
Section: Structure Of the Xaxab Pore Complexmentioning
confidence: 99%